Case Report: Treating Severe Atrophic Maxillary Arch with Horizontal Ridge Augmentation - Gurjar KA (Dove Medical Press, 2021)
Kavish A Gurjar State of the Art Dental Group, Rockville, MD, 20850, USACorrespondence: Kavish A GurjarState of the Art Dental Group, Rockville, MD, 20855, USATel +1 8187465914Email Drkavishagurjar@gmail.comAbstract: A deficient maxillary edentulous ridge volume can be augmented by onlay grafting technique for implant placement to support fixed hybrid screw retained prosthesis. Various techniques have been used to correct defective bone. These augmentation techniques include inlay and onlay grafts, bone splitting osteotomy, and distraction osteogenesis, among others. Successful reconstruction depends on multiple biological factors as well as patient compliance. Here, I report a case of ridge augmentation using onlay cortico-cancellous particulate bone grafting, resorbable collagen membrane, and bone tac pins, followed by surgical implant placement with multiunit abutments to support the fixed prosthesis.Keywords: atrophy, medullary bleeding, dental implant, ridge augmentation, bone grafting, guided bone regeneration, GBR, collagen membrane